Analytical formulae and applications of vertical dynamic responses for railway vehicles - Yu, Yuewei (Strojniški vestnik, 2023)
To effectively improve the estimated level of railway vehicles’ vertical dynamic responses and provide a more suitable reference for the selection of its secondary suspension damping parameter, this paper has derived the root mean square values analytical formulae of the car body vertical acceleration, the secondary suspension vertical stroke, and the axle box vertical action force for railway vehicles under the random excitation of the track closer to the actual track characteristics. The correctness of the analytical formulae is verified by testing a real vehicle. Then, according to the analytical formulae derived, an analytical design method of the optimal damping ratio for the secondary suspension system is constructed based on the multi-objective programming and single-objective interval constraint analysis, which can be used to find the best trade-off for conflicting performance indices, such as ride comfort, running smoothness, and running safety, and the influences of the system parameters on the optimal damping ratio are analysed. This research can effectively characterize the vertical vibration response of railway vehicles and provide an effective reference for the initial design of the railway vehicle secondary suspension damping parameter.
Keywords: analiza vpliva stopnje blaženja; damping parameter design; izpeljava modela; model deduction; optimal compromise; optimalen kompromis; projektiranje parametrov blaženja; railway vehicle; vertical dynamic response; vertikalni dinamični odgovor; železniško vozilo